Radiosensitivity in the breast cancer management scenario: another step forward? - Meattini, Icro; Francolini, Giulio; Livi, Lorenzo (Journal of Thoracic Disease, 2016)
We have recently read with interest the paper by Torres-Roca and colleagues (1); some relevant issues related to treatment tailoring on the basis of molecular signatures may raise considering showed results.